The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.meatsci.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The chemical and sensory qualities of smoked blood sausage made with the edible by-products of goat slaughter

Abstract: The aim was to evaluate smoked blood sausage prepared using goat blood (50%), viscera (10%) and meat fragments (20%). Microbiological, chemical and sensory evaluations were conducted. The quality analyses showed that smoked goat blood sausage is rich in high biological value proteins, amino acids, essential fatty acids, and iron (26.65mg/100g). The smoked goat blood sausage was rated to have a sensory acceptance of greater than 80%. The use of edible by-products from the slaughter of goats in the formulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 20 publications
5
30
2
1
Order By: Relevance
“…The average fat content was lower than the average (10.43%) obtained for buchadas from five cities in the state of Paraíba (Santos et al, ), but closer to the average of 4.99% obtained by other authors for buchadas under different forms of storage (Queiroz et al, ). In addition, Silva et al () observed similar fat content in smoked goal chorizo (9.97%) and Morcilla de Burgos (10.83% (Spanish blood sausage), whereas higher fat content were noticed for Morcilla de León (14.24%). Finally, Brasil et al () reported fat content values ranged from 3.62% to 11.87% in goat “sarapatel” (a traditional meat product made from blood and viscera).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The average fat content was lower than the average (10.43%) obtained for buchadas from five cities in the state of Paraíba (Santos et al, ), but closer to the average of 4.99% obtained by other authors for buchadas under different forms of storage (Queiroz et al, ). In addition, Silva et al () observed similar fat content in smoked goal chorizo (9.97%) and Morcilla de Burgos (10.83% (Spanish blood sausage), whereas higher fat content were noticed for Morcilla de León (14.24%). Finally, Brasil et al () reported fat content values ranged from 3.62% to 11.87% in goat “sarapatel” (a traditional meat product made from blood and viscera).…”
Section: Discussionmentioning
confidence: 87%
“…Five sheep buchadas , each weighing approximately 130 grams, were used for the sensory analysis. The sensory analysis was performed using the methodology adapted from Silva et al (). After cooking, the samples were splitted into equal portions of 30 g into polystyrene cups (70 ml), topped with foil and marked with a random 3‐digit code.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em estudo realizado por Ferreira et al (2013) A força de cisalhamento obtida para queijo de porco foi de 7,8± 1,68 N conforme apresentado na tabela 3. Em artigo publicado por Silva et al (2013), especificamente para morcela (Morcilla de Leon), os autores obtiveram valores de 10,7 ± 4,23 N. A força de cisalhamento inferior para o queijo de porco pode estar relacionada ao fato que na sua formulação a presença de pele eleva a concentração de colágeno, que sofre gelatinização durante a cocção, causando redução no cisalhamento.…”
Section: Resultsunclassified
“…It is used in the preparation of cooked ham and hot dogs to provide lighter color to the product (Autio, Lyytikainen, Malkki, & Kanko, 1985). Moreover, goat blood and viscera are also used to prepare smoked blood sausages with high protein quality, high sensory acceptance and high level of iron present in the product (Silva et al, 2013). Blood plasma contains 60% albumin and has the capability to form gel (Silva & Silvestre, 2003).…”
Section: Blood and Plasma Utilizationmentioning
confidence: 99%